2002
DOI: 10.3354/ame028239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen partial pressure and salinity on the community composition of ammonia-oxidizing bacteria in the Schelde estuary

Abstract: The influence of environmental factors on the community structure of ammoniaoxidizing bacteria (AOB) was investigated in the Schelde estuary. Simultaneously with the increase of oxygen and salinity, a shift of the dominant AOB was observed. Molecular analysis based on 16S rRNA genes showed that the freshwater area was dominated by Nitrosomonas-like sequences which were closely related to N. ureae and N. oligotropha. In the brackish area, sequences of a novel group of Nitrosomonas-like bacteria and relatives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
5
65
1
Order By: Relevance
“…N. mobilis, probably introduced by tidal cycles, was found in samples taken within the salinity gradient (1 to 8 0 / 00 ) and was characteristic of the downstream estuary at low tide. The closest relatives reported were some uncultured AOB such as clone K_8 (99% homology), collected in surface sediments from Denmark Fjord, where the salinity value was 14 0 / 00 (40); clone LD1-B6 (98% homology), found in anoxic marine sediments (21); and DGGE band 423 (98% homology), obtained from the Schelde estuary water with a low ammonia level and high salinity (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N. mobilis, probably introduced by tidal cycles, was found in samples taken within the salinity gradient (1 to 8 0 / 00 ) and was characteristic of the downstream estuary at low tide. The closest relatives reported were some uncultured AOB such as clone K_8 (99% homology), collected in surface sediments from Denmark Fjord, where the salinity value was 14 0 / 00 (40); clone LD1-B6 (98% homology), found in anoxic marine sediments (21); and DGGE band 423 (98% homology), obtained from the Schelde estuary water with a low ammonia level and high salinity (7).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the freshwater estuary, a new AOB (band C) was selected in the sector of maximum nitrifying activity where oxygen and ammonia concentrations decrease and suspended-matter concentrations increase. Whereas many studies have shown that oxygen has no effect on the composition of the AOB community (4,7,32), the "band C" population may thrive on freshly produced ammonia, organic compounds, or new mineral ions (14) specific to the estuary, where the organic-matter turnover is generally high (23,50). This niche differentiation may be due to physiological differences such as the ability to produce extracellular polymeric substances (57), allowing an attached versus free-living AOB selection (42).…”
Section: Vol 70 2004 Dgge Analysis Of Ammonia Oxidizers In the Seinmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the genus Nitrosomonas, AOB form several clusters that can be distinguished by ecophysiological characteristics, such as affinity for NH 4 ϩ and tolerance to increasing salt or NO 2 Ϫ concentrations (1,6,12). Nitrosomonas cluster 6a is comprised of AOB adapted to low ammonium (NH 4 ϩ ) concen-trations that can be found in a range of environments (13)(14)(15)(16)(17). Nitrosomonas sp.…”
mentioning
confidence: 99%
“…Dong and Nedwell 2006). In addition to the supply of oxygen and ammonia, which are the main controls on nitrification, other environmental variables may affect this biological process: temperature (Dai et al 2008), salinity (Bollmann and Laanbroek 2002) and pH (Strauss et al 2002).…”
Section: Introductionmentioning
confidence: 99%